Green Tea Extract Supplementation Induces the Lipolytic Pathway, Attenuates Obesity, and Reduces Low-Grade Inflammation in Mice Fed a High-Fat Diet - Cláudio A. Cunha; Fábio S. Lira; José C. Rosa Neto; Gustavo D. Pimentel; Gabriel I. H. Souza; Camila Morais Gonçalves da Silva; Cláudio T. de Souza; Eliane B. Ribeiro; Alexandra Christine Helena Frankland Sawaya; Cláudia M. Oller do Nascimento; Bruno Rodrigues; Patrícia de Oliveira Carvalho; et al. (Hindawi Limited, 2013)
The aim of this study was to evaluate the effects of green tea Camellia sinensis extract on proinflammatory molecules and lipolytic protein levels in adipose tissue of diet-induced obese mice. Animals were randomized into four groups: CW (chow diet and water); CG (chow diet and water + green tea extract); HW (high-fat diet and water); HG (high-fat diet and water + green tea extract). The mice were fed ad libitum with chow or high-fat diet and concomitantly supplemented (oral gavage) with 400 mg/kg body weight/day of green tea extract (CG and HG, resp.). The treatments were performed for eight weeks. UPLC showed that in 10 mg/mL green tea extract, there were 15 μg/mg epigallocatechin, 95 μg/mg epigallocatechin gallate, 20.8 μg/mg epicatechin gallate, and 4.9 μg/mg gallocatechin gallate. Green tea administered concomitantly with a high-fat diet increased HSL, ABHD5, and perilipin in mesenteric adipose tissue, and this was associated with reduced body weight and adipose tissue gain. Further, we observed that green tea supplementation reduced inflammatory cytokine TNFα levels, as well as TLR4, MYD88, and TRAF6 proinflammatory signalling. Our results show that green tea increases the lipolytic pathway and reduces adipose tissue, and this may explain the attenuation of low-grade inflammation in obese mice.